Back Cover: Electrochemical Cycling of Sodium‐Filled Silicon Clathrate (ChemElectroChem 2/2014). Issue 2 (11th February 2014) - Wagner, Nicholas A.; Raghavan, Rahul; Zhao, Ran; Wei, Qun; Peng, Xihong; Chan, Candace K.
<x xml:space="preserve">Abstract</x> The picture shows lithium insertion into a Type‐II clathrate, Na24Si136 , which is evaluated as an anode for lithium‐ion batteries and studied with X‐ray diffraction and first principles methods by C. K. Chan et al. on p. 347.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>